Design Of Employee Attendance System Based On RFID And IOT Technology Case Study PT XYZ - Berliyanto, Berliyanto; Nurrohman, Aji; Wibisono, Sigit; Darma, Surya; Asrar, Leni Devera; Budi Santoso, Triyono (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
Employee attendance management is an important business process that needs to be done by most companies in general. The utilization of an employee attendance information system can overcome problems related to these business processes such as ineffective processes because they are still done manually, high risk of data manipulation, or complicated recapitulation preparation. The development of the system requires an analysis and design process to minimize the risk of implementation failure. The focus of this research is to design an employee attendance system that can meet the needs of the company in general. This research is a case study research conducted at PT XYZ. The methodology used follows the stages in the software development life cycle (SDLC). The results obtained are a list of system requirements in the form of user stories, system designs, and a prototype system developed with RFID and Internet of Thing (IOT) technology. Testing with scenario-based testing techniques was also carried out on the prototype.